Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Charla | Estética afro Identidad, saberes y resistencia - Banrepcultural (2019)
En esta charla conversaremos sobre las luchas históricas por la reivindicación de los derechos del pueblo afro que están detrás de su estética, específicamente en dos de sus expresiones femeninas: el turbante afro y el pelo natural, los cuales han servido como elementos de resistencia para la pervivencia de las prácticas y costumbres ancestrales. Como parte de la exposición temporal del Museo del Oro 'A bordo de un navío esclavista, La Marie-Séraphique' (que se presentó en Bogotá del 7 de octubre de 2018 al 7 de abril de 2019) hablamos en el museo sobre algunos peinados ancestrales, como la espina de pescado, las tropas, el hundidito, el ciempiés y la vicha, y sobre los usos, significados y modelos de los turbantes afro, como la cadena del esclavo, la autoridad, el kitambala, el enkeycha y el doek. El termino mata ‘e pelo surge de las expresiones propias de nuestras ancestras, que se referían al pelo afro cómo una gran mata (árbol), frondosa, incontrolable y rizada, que requería unos cuidados particulares por su condición crespa, abundante y diversa. El cuerpo de la mujer negra, raizal y palenquera ha estado históricamente ligado a las luchas por la reivindicación de los derechos del pueblo afro, siendo la mata ‘e pelo el elemento estético que más las ha transmitido. Entre las personas de ancestros africanos, la estética del pelo afro se remonta a un pasado cargado de lucha y resistencia, pues las trenzas fueron usadas para la elaboración de mapas que marcaban el camino a la libertad de los cimarrones. Las mujeres se reunían en el patio para peinar a las más pequeñas. Diseñaban en su cabeza un mapa lleno de caminitos y salidas de escape, en el que ubicaban los montes, ríos y árboles más altos. Así, al verlas, los hombres sabían cuáles rutas tomar. Su código, desconocido para los amos, les permitía a los esclavizados huir. El balance humano de la trata de cautivos africanos a través del Atlántico es dramático: con una inmensa brutalidad, desplazó a 13 millones de hombres, mujeres y niños entre la segunda mitad del siglo XVI y finales del siglo XIX. #ElMuseoDelOroTambiénEsAfro Producción Banco de la República Realización Santiago Martínez
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

The Decolonial Turn in Media Studies in Africa and the Global South - Moyo, Last (Palgrave Macmillan, 2020)
This book develops a nuanced decolonial critique that calls for the decolonization of media and communication studies in Africa and the Global South. Last Moyo argues that the academic project in African Media Studies and other non-Western regions continues to be shaped by Western modernity’s histories of imperialism, colonialism, and the ideologies of Eurocentrism and neoliberalism. While Africa and the Global South dismantled the physical empire of colonialism after independence, the metaphysical empire of epistemic and academic colonialism is still intact and entrenched in the postcolonial university’s academic programmes like media and communication studies. To address these problems, Moyo argues for the development of a Southern theory that is not only premised on the decolonization imperative, but also informed by the cultures, geographies, and histories of the Global South. The author recasts media studies within a radical cultural and epistemic turn that locates future projects of theory building within a decolonial multiculturalism that is informed by trans-cultural and trans- epistemic dialogue between Southern and Northern epistemologies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; _Nettoyé

Por uma pedagogia crioula : memória, identidade e resistência no quilombo de Conceição das Crioulas – PE - Nascimento, Márcia Jucilene do (Universidade de Brasília, 2017)
This dissertation aims to describe the specific schooling process developed in the quilombo of Conceição das Crioulas, in Salgueiro / PE. This process was a result of the socio-historical reconstruction movement of the quilombo’s history, which started in the 1980s. This process triggered several conflicts, and priority was given to the regaining of their territory and to the search for educational practices with decolonizing ideals. Based on the individual and collective memories of Conceição das Crioulas people, we have registered the historical accounts of the community’s resistance to the domination and oppression systems imposed to them since the arrival of the creole founders until today. The methodological trajectory was based on interviews, informal conversations and the analysis of a video-documentary, specifically recorded for this research. This path also allowed us to evaluate how we have perceived and done our school education over a period of twenty-two years, whose milestone is the inauguration, in 1995, of Professor José Mendes school, a local public school where grades 6th to 9th are taught. First, this paper addresses important elements for the beginning of this search. Next, it describes practices and specific actions of the education of Conceição das Crioulas. After that, it draws a comparative analysis about this and other pedagogical experiences, highlighting connections and significant distances between them. Finally, at the end of the last chapter, it conceptualizes this experience, which was named Crioula Pedagogy in the community.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; _À analyser